Delivering an iterative Communication Partner Training programme to multidisciplinary healthcare professionals: A pilot implementation study and process evaluation. Issue 3 (5th April 2021) - Shrubsole, Kirstine; Lin, Tz‐Jie; Burton, Christine; Scott, Julie; Finch, Emma
Abstract: Background: Despite evidence that Communication Partner Training (CPT) can enable health professionals to communicate more effectively with people with aphasia (PWA), an evidence–practice gap exists. To address this, a tailored implementation intervention was developed and trialled to improve health professionals' implementation of communication strategies in a subacute setting. Aims: To explore the outcomes and perceived feasibility, acceptability and potential effectiveness of an iterative CPT implementation intervention on multidisciplinary healthcare professionals' communication with PWA. Methods & Procedures: The CPT implementation intervention was delivered to two groups of healthcare professionals ( n = 6 and 7) approximately 6 months apart. The intervention underwent two iterations targeting emerging barriers to implementation success, with Group 2 receiving a modified version of the Group 1 intervention. A concurrent qualitative process evaluation was conducted to understand key factors determining implementation outcomes. Quantitative outcomes were recorded at baseline and 3‐month follow‐up, including the Measure of Skill in Supported Communication (MSC), a customized behavioural determinants survey mapped to the Theoretical Domains Framework (TDF) and the Organizational Readiness for Change survey. Focus groups and semi‐structured interviews were conducted with health professional participants and the speech–language therapist trainer to explore perceptions of feasibility, acceptability and potential effectiveness. Content analysis was used to analyse the qualitative data, with categories and themes generated. Outcomes & Results: The Group 2 implementation intervention was adapted based on feedback and reflections from Group 1 participants to incorporate more time for practice interactions and discussion during training, individual follow‐up sessions and provision of accessible resources to aid communication attempts. There were greater improvements seen in the Group 2 outcomes on both the MSC and the TDF survey, suggesting that the iterative tailoring of the intervention was successful in addressing the barriers to change and led to improved implementation. The difference between the group's outcomes may also partly be explained by the impact of organizational readiness, which decreased during Group 1's implementation period. Despite similar themes emerging from the stakeholder perspectives in both groups (training factors, implementation facilitators, implementation barriers, and changes in knowledge and practice), these diverted in ways which served to explain the different implementation outcomes. Conclusions & Implications: An iteratively adapted CPT implementation intervention targeting healthcare professionals' use of supported communication strategies was feasible and acceptable for most participants. The implementation intervention was potentially effective in changing participants' communication with PWA, particularly for Group 2. Future CPT implementation efforts should continue to incorporate stakeholder input and tailor strategies to the organizational context, and measure whether outcomes are sustained in the long term. What this paper adds What is already known on the subject: CPT is a complex intervention that can improve communication access and outcomes for PWA. However, there are barriers to both delivering CPT programmes to staff, and for staff in modifying their communication behaviours. Despite increasing efforts to improve CPT implementation, it remains largely unclear whether CPT implementation interventions are effective in improving interactions between staff and patients, and what elements of an implementation intervention result in changed behaviour. What this study adds to existing knowledge: This study showed that adopting an iterative, barriers‐focused approach to implementation facilitated practice change for one of the groups that participated in the programme. Incorporating stakeholder feedback in an ongoing way led to improvements in feasibility, acceptability and potential effectiveness, with several of the main barriers being effectively addressed by the intervention. Some key mechanisms of change were identified. What are the potential or actual clinical implications of this work: It is necessary to develop active, targeted implementation strategies to support healthcare professionals to modify their communication, monitor implementation barriers as they arise and modify behaviour‐change strategies accordingly. In a similar context, it is suggested that CPT implementation interventions should incorporate the use of audit feedback, physical resources and educational lectures paired with interactions with PWA in order to bring about change, with ongoing support and facilitation.